Digitalisasi Keuangan: Pelatihan Pencatatan Laporan Keuangan UMKM dengan Bantuan Aplikasi BukuWarung - Harrie Yudha Pahlawan (CV. ITTC INDONESIA, 2026)
This Field Work Practice (PKL) activity aimed to assist the MSME partner, Pempek Cek Lisa, in improving financial management efficiency through the implementation of a simple accounting system. In the digital era, various free and user-friendly financial management applications have become available. However, many MSMEs still face challenges in financial reporting due to limited time and a lack of understanding of the importance of financial reporting, leading them to rely on manual bookkeeping. To address this issue, the authors introduced BukuWarung, a digital financial management application, as a practical solution for more efficient financial record-keeping. This activity was conducted with Pempek Cek Lisa, a culinary MSME that plays an important role in the local economy but has limited awareness of the importance of financial reporting and technology adoption. The implementation methods included interviews, educational outreach, and direct mentoring for the business owner. The results showed that the MSME gained a better understanding of the importance of financial management and successfully adopted BukuWarung for financial record-keeping. In conclusion, this project successfully introduced BukuWarung as a tool to enhance financial awareness and improve financial management capabilities.